Children’s View of Violence in the Media: Video Games, Television and Music - Castro Pérez, Marianella (2013)
The purpose of this research article is to generate awareness and self-analysis regarding the role played by adults with respect to violence in the media and the risk and protective factors associated with it, in order to propose a proactive approach that ensures children and adolescents a comprehensive development in environments that promote the right to peace. The research was descriptive and explanatory with a mixed approach (qualitative and quantitative). The study was conducted with 390 students (from 1st to 11th grades) in all provinces of Costa Rica, except Guanacaste. For data collection, two questionnaires with open and closed questions were designed and applied to the students. Based on the answers provided by the participants, the researchers prepared manuals of categories, tables, descriptions, and data analysis. This paper will contribute to find solutions and alternatives for those working directly or indirectly with children to be able to deal with violence in the media in a more assertive manner, giving children the opportunity of a good quality of life and a peaceful coexistence in the society.